Digitalization in the operating theatre- an interview study of operating room nurses’ and nurse anesthetists’ experiences in Norway - Ann-Chatrin Linqvist Leonardsen; Vivian Nystrøm; Anne Kristin Hole Trollnes; Renate Slang; Eilen Olsen (BMC Nursing)
Abstract Background Digitalization in the health sector requires adaptive change in human attitudes and skills. The operating theatres have been introduced to digital innovations through centuries. The aim of this study was to explore operating room (OR) nurses’ and Nurse Anesthetists’ (NAs) experiences with digitalization in the operating theatre. Methods The study had a qualitative design, using individual interviews with OR nurses and NAs at a Norwegian hospital. Data were analyzed using reflexive thematic analysis in-line with recommendations from Braun & Clarke. Results Two themes were identified, namely (1) Impacting the work processes, and (2) Implications for patient safety. The OR nurses and NAs experienced that digitalization impacted on their work processes positively through making these smoother, but also negatively making the work processes vulnerable for disruptions, leading to a need for parallel actions. Digitalization was experienced to positively impact patient safety for example through making information more accessible. However, digital tools reduced focus on the patient, and then represented a risk to patient safety. Conclusion OR nurses and NAs perceive that digitalization on one side may facilitate work processes and information flow. However, on the other side digitalization may steel focus on the patient. These aspects should be taken into consideration in quality improvement initiatives and when introducing new digital tools.